Social norm perception in economic laboratory experiments: inexperienced versus experienced participants [dataset] - Schmidt, Robert J. (Universität, 2019)
We study whether social norm perception in economic laboratory experiments differs between inexperienced and experienced participants. We find substantial differences between the two groups both regarding injunctive and descriptive social norms in the context of participation in laboratory experiments. By contrast, social norm perception for the context of daily life does not differ between the two groups. We therefore conclude that learning effects are more important than selection effects for explaining differences between inexperienced and experienced participants. We also conduct exploratory analyses on the relation between lab and field norms and find that behaving unsocial in the lab is considered substantially more appropriate than in the field. This appears inconsistent with the hypothesis that social preferences measured in lab experiments are inflated and indicates a distinction between revealed social preferences as elicited commonly and the elicitation of normatively appropriate behavior.
Gesehen am 27.03.2019
Keywords: Forschungsdaten; Datenbank